Q: How do you find y intercept?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

solve the x and you find the y

To find the y intercept put zero in for x and solve. To find the x intercept put zero in for y and solve. (0,8) and (-8,0)

The function y = -1 has no x-intercept; its graph is a horizontal line with a y-intercept of -1.

To find the x-intercept, plug 0 in for y: 0 = -x-1, so x = -1. To find the y-intercept, plug zero in for x: y=-0-1, so y = -1 The x-intercept is (0,-1) and the y-intercept is (-1,0)

Normally, the y-intercept would be after the x term, but because there is no x term the y-intercept is 0.

Related questions

solve the x and you find the y

To find the y intercept put zero in for x and solve. To find the x intercept put zero in for y and solve. (0,8) and (-8,0)

The function y = -1 has no x-intercept; its graph is a horizontal line with a y-intercept of -1.

to find the y-intercept you plug in your x and y values in to the equation of y=mx+b. b is the y intercept and m is the slope. To find the x-intercept, set y = 0, and find value of x that satisfies the equation. If it is a line in the form y=mx+b, then the x-intercept will be at x= -b/m

if you are looking at a graph the y intercept is when the graph crosses the y axis and the x intercept is when the graph crosses the x axis. if you have a formula... plug zero in for x to find the y intercept, and plug zero in for y to find the x intercept

To find the x-intercept, plug 0 in for y: 0 = -x-1, so x = -1. To find the y-intercept, plug zero in for x: y=-0-1, so y = -1 The x-intercept is (0,-1) and the y-intercept is (-1,0)

8

To find the y-intercept you substitute in 0 for x and solve. To find the x- intercept you substitute in 0 for y and solve. If you do it correctly you should find the x-intercept to be -3 and the y-intercept to be 3.

To find the x-intercept you need to set y=0 in your equation. To find the y-intercept you need to set x=0 in your equation.

Normally, the y-intercept would be after the x term, but because there is no x term the y-intercept is 0.

To find the y-intercept, plug 0 in for x: 3y = -12 y = -4To find the x-intercept, plug 0 in for y: 2x = -12 x = -6The y-intercept is y = -4, and the x-intercept is x = -6.

At the y-intercept, x=0 and y = b .